Are fixed-term jobs bad for your health? A comparison of West-Germany and Spain - Gash, Vanessa; Mertens, Antje; Romeu Gordo, Laura (Nürnberg, 2006)
"In this paper we analyse the health effects of fixed-term contract status for men and women in West-Germany and Spain using panel data. This paper asks whether changes in the employment relationship, as a result of the liberalisation of employment law, have altered the positive health effects associated with employment (Goldsmith et al. 1996, Jahoda 1982). Using information on switches between unemployment and employment by contract type we analyze whether transitions to different contracts have different health effects. We find that unemployed workers show positive health effects at job acquisition, and also find the positive effect to be smaller for workers who obtain a fixed-term job. We also establish surprising differences by gender and country, with women less likely to report positive health effects at job acquisition. For West-Germany, this was found to be a function of the dual-burden of paid and unpaid care within the home."